2006
DOI: 10.1161/01.str.0000231389.34701.b5
|View full text |Cite
|
Sign up to set email alerts
|

The ALIAS Pilot Trial

Abstract: Background and Purpose-High-dose human albumin (ALB) is robustly neuroprotective in rodent stroke models. A phase I dose-escalation study was conducted to assess the safety of ALB therapy in ischemic stroke. We analyzed the data for preliminary evidence of treatment efficacy. Methods-Eighty-two subjects with acute ischemic stroke (NIH Stroke Scale [NIHSS] of 6 or above) received 25% ALB beginning within 16 hours of stroke onset. Six successive ALB dose tiers were assessed (range, 0.34 to 2.05 g/kg). Forty-two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(60 citation statements)
references
References 30 publications
1
59
0
Order By: Relevance
“…The ALIAS pilot trial suggested a favorable outcome when thrombolysis was combined with albumin. 100 Synergistic effects of albumin with thrombolysis were also demonstrated in a study using a rat stroke model in which the combination therapy improved microvascular hemodynamics.…”
Section: Candidate Drugs For Acute and Chronic Stroke Treatment Albuminmentioning
confidence: 89%
See 1 more Smart Citation
“…The ALIAS pilot trial suggested a favorable outcome when thrombolysis was combined with albumin. 100 Synergistic effects of albumin with thrombolysis were also demonstrated in a study using a rat stroke model in which the combination therapy improved microvascular hemodynamics.…”
Section: Candidate Drugs For Acute and Chronic Stroke Treatment Albuminmentioning
confidence: 89%
“…The authors of that study interpreted the results as a sign for efficacy, based on comparison of higher doses with lower doses and in comparison with a historical control group. 99,100 A randomized, multicenter, double-blind, placebocontrolled trial (ALIAS Phase III Trial, www.clinicaltrials. gov; NCT00235495) is currently being conducted.…”
Section: Candidate Drugs For Acute and Chronic Stroke Treatment Albuminmentioning
confidence: 99%
“…Proposed beneficial effects of higher serum albumin level include binding to free fatty acids, inhibition of oxygen radical production and support of endothelial function. Recent clinical study suggests that 25% human albumin in doses ranging up to 2.05 g/kg is well tolerated by patients with acute ischemic stroke and may have beneficial effect on stroke outcome Palesch et al, 2006). Patients with low serum albumin could be a risk of severe stroke due to the insufficient neuroprotection mediated by albumins.…”
Section: Hypoalbuminemia In Acute Ischemic Stroke Patients T Dziedzicmentioning
confidence: 99%
“…Recent data from a phase I dose-escalation study provide evidence that human serum albumin is safe after stroke, despite a mild-to-moderate increase in pulmonary edema, even when given with thrombolytic therapy (26). The study provided preliminary evidence of efficacy, with patients in the highest dose tiers having about an 80% greater chance of good outcome at 3 months than the lower dose tiers (57). There also seemed to be a synergistic effect between albumin and thrombolytic therapy.…”
Section: Fig 3 Ischemia Results In Rapid Loss Of High-energy Phosphmentioning
confidence: 99%